Religious Beliefs of Parents: Implication for the Child Rights Act, 2003 in Nigeria - Adeyeye, Joel (UDUS LAW JOURNAL, 2020)
This article undertakes a critical study of the religious beliefs of parents as it affects the rights of the child. Every human being, be it an adult, male or female has rights that are domiciled in him/her as a creator of God. Children for being what they are cannot on their own enforce these rights. Right from the Universal Declaration of Human Rights (UDHR) and other international legal instruments, to the Regional legal instruments like the African Charter on Human and Peoples' Rights; the sub regional legal instrument like the Economic Community of West African States (ECOWAS), to the domestic law of each country; for example, the Constitution of the Federal Republic of Nigeria, 1999 (as amended); The child's Rights Act, 2003 and which various States of the Federation has domesticate these Law. This article therefore seeks to interrogate these laws as a result of the recent decision of the Supreme Court of Nigeria's decision in the case Esabunory Fayewa[2019] 7 NWLR (pt 1671) 316. It is recommended that the government should review the aspect of age disparity in our Laws with a view to making a particular age workable for the purpose of implementing the Child Rights Act.In interrogating these Laws, judicial pronouncements from other jurisdictions other than Nigeria shall also be considered.
Keywords: Religion; Child Rights Act; Beliefs; Implications